Excess mortality and COVID-19 deaths: preliminary data from Serbia and comparison with European experience - Arsenović, Daniela (Geographica Pannonica, 2023)
Mortality statistics is underlay for public health measures and action and consequently it is one of the major indicator in measures of Covid-19 impact on population. This study aim to explore excess mortality during the Covid-19 pandemic in Serbia. Excess mortality compares expected and observed number of deaths during the given period. Analysis in this paper was based on excess deaths and excess mortality rate. Data was downloaded from the national COVID-19 database and obtained from a relevant source from the Statistical Office of the Republic of Serbia. In order to provide better understanding of excess death, the excess mortality rate was calculated for the period January 2015-June 2022. For the period January 2015-February 2020, 38 months were observed without excess deaths, while in months with excess deaths, almost in all months excess mortality rate was below 12%. Since March 2020, the excess mortality rate has increased significantly, with highest values in December 2020 (91.4%), October (84.3) and November (67.8) 2021.
Keywords: excess mortality rate; Covid-19; pandemic; Serbia